(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2018)
The author participated as a jury member in the final evaluation of the Workshop held in the opportunity of the 2014 UIA Congress in the city of Durban. Author positively evaluates the contribution of the workshop to the future evolution of the city.